A novel method to assess subchondral bone formation using [18F]NaF-PET in the evaluation of knee degeneration. Issue 5 (May 2018) - Jonnakuti, Venkata S.; Raynor, William Y.; Taratuta, Elena; Werner, Thomas J.; Alavi, Abass; Baker, Joshua F.
Abstract : Purpose: Fluorine-18-sodium fluoride-PET ([ 18 F]NaF-PET) facilitates direct assessment of subchondral bone formation to evaluate degeneration in articulating joints. No standards exist for the quantification of joint activity using [ 18 F]NaF-PET, and many techniques rely on focal uptake to characterize an entire region of interest. This study proposes a novel method of quantitative global knee analysis to assess regions of expected bone remodeling in the evaluation of knee degeneration. Patients and methods: The study population consisted of 18 patients with rheumatoid arthritis who underwent [ 18 F]NaF-PET/computed tomography imaging. The maximum standardized uptake value (knee SUVmax ) in addition to a target-to-background ratio (TBR) that represents global knee activity adjusted for systemic bone formation measured at the lateral femoral neck (global knee TBR) were calculated. A radiologist scored standard radiographs of the knee in nine patients using the Kellgren–Lawrence grading system. Results: Patients with greater [ 18 F]NaF uptake demonstrated greater knee deterioration, which was corroborated by the radiograph findings. Average Kellgren–Lawrence grading was strongly associated with both global knee TBR (Spearman ρ =0.69, P =0.04) and knee SUVmax scores (Spearman ρ =0.93, P =0.0003). Conclusion: Assessment of global activity within the joint is a feasible and clinically useful technique for characterizing disease activity with a single value. Furthermore, a ratio based on systemic bone turnover in a nonarticulating, weight-bearing site adjusts for differences in bone formation related to bodyweight or metabolic bone diseases. We hypothesize that a global knee TBR score may be more sensitive at detecting changes in disease progression, as new spatially distinct lesions with a lower SUV that develop within an region of interest would not be detected by the SUVmax methodology. Longitudinal studies assessing sensitivity with larger patient cohorts are needed to further validate this methodology.